Antenatal glucocorticoids and neonatal inflammation-associated proteins. (December 2016) - Faden, Maheer; Holm, Mari; Allred, Elizabeth; Fichorova, Raina; Dammann, Olaf; Leviton, Alan; ,
Highlights: Antenatal glucocorticoids have no sustained anti-inflammatory effects on extremely low gestational age infants. Preterm Infants born to mothers with strong inflammatory stimuli are more likely to be exposed to a complete course of antenatal glucocorticoids. Antenatal glucocorticoids could depress the preterm infant immunity during the 1st week of life. Abstract: Background: To date, studies of the relationship between antenatal glucocorticoids (AGC) and neonatal inflammation in preterm newborns have been largely limited to umbilical cord blood specimens. Aim: To explore the association between exposure to antenatal glucocorticoids and concentrations of inflammation-related proteins in whole blood collected from very preterm newborns at multiple times during the first postnatal month. Methods: We measured the protein concentrations on postnatal day 1 (N = 1118), day 7 (N = 1138), day 14 (N = 1030), day 21 (N = 936) and day 28 (N = 877) from infants born before the 28th week of gestation and explored the relationship between antenatal steroid receipt and protein concentrations in the highest and lowest quartiles. The creation of multinomial logistic regression models (adjusted for potential confounders) allowed us calculate odds ratios and 95% confidence intervals. Results: Twenty of 420 assessments [21 (proteins) × 2 (exposure levels: partial and full) × 2 (quartile levels: top and bottom) × 5 (days)] were statistically significant without any cohesive pattern. Conclusion: Among infants born before 28 weeks of gestational age, neither full, nor partial courses of antenatal glucocorticoids have a sustained anti-inflammatory effect.